Sex Differences in Incidence and Risk Factors for Delayed Cerebral Ischemia Following Aneurysmal Subarachnoid Hemorrhage: A Propensity Score‐Matched Analysis - Chao Zhang; Wenjuan Tang; Pengzhan Yin; Chen Yang; Xintong Zhao; Xinggen Fang; Mingquan Ye; Yunfeng Zhou (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Aneurysmal subarachnoid hemorrhage exhibits higher prevalences in women. However, it remains unclear whether this disparity is correlated with delayed cerebral ischemia (DCI) incidence and accompanying risk factors. We aimed to clarify the sex differences in incidence and risk factors for DCI following aneurysmal subarachnoid hemorrhage. Methods We included consecutive patients with aneurysmal subarachnoid hemorrhage who underwent endovascular coiling in a prospective database from November 2015 to September 2023. DCI was defined using the 2010 Multidisciplinary Research Group definition. Propensity score matching and multivariate logistic regression were employed to mitigate confounders and identify risk factors, respectively. Subgroup analyses were performed to further evaluate sex differences by age groups. Results Among the 905 patients included, 215 women were matched with 215 men after propensity score matching. Women exhibited a higher DCI incidence than men (64.6% versus 35.4%, odds ratio [OR], 2.17 [95% CI, 1.39–3.45]; P<0.001). In addition to acute hydrocephalus and modified Fisher Score, the 2 shared independent risk factors for both sexes. Age (OR, 2.66 [95% CI, 1.56–4.66]; P<0.001), fasting glucose (OR, 1.15 [95% CI, 1.06–1.24]; P<0.001), Hunt–Hess grade (OR, 3.18 [95% CI, 1.61–6.41]; P<0.001), intracerebral hematoma (OR, 2.40 [95% CI, 1.29–4.51]; P=0.006), and transit time to the center of the impulse response function (OR, 1.49 [95% CI, 1.09–2.08]; P=0.017) were additional risk factors for women. There was no interaction between sex and each risk factors on DCI (all P for interaction >0.05). Conclusions Women exhibited a significantly higher tendency for DCI compared with men. Furthermore, sex‐specific differences in DCI risk factors may be useful for risk stratification.